STUDENT RESPONSIBILITIES IN DISTANCE LEARNING IN ELEMENTARY SCHOOL AGES 10 TO 11 YEARS - Lestari, Ika; Nafiah, Maratun; Zahara, Adinda (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2021)
When school students are required to stay at home, as is the case with the current COVID-19 pandemic, parents need good parenting skills and a good level of education. Apart from monitoring the temperament and performance of their children, parents should try to meet their children's educational needs as effectively as possible. This study aims to provide a basis for decisions about data preparation and analysis and how the research results should be interpreted and reported. Thus, the main problem addressed in this study is the attitude of students' responsibility in distance learning. The type of research used is a descriptive quantitative research that only uses one variable, namely the attitude of responsibility. The results of this study concluded that students could make their own decisions, being able to keep time, being able to complete assigned tasks, being able to get through difficult times, being able to accept the consequences, and learn from failure.